Cross-sectional and longitudinal associations of adherence to WCRF/AICR cancer prevention recommendations with health-related quality of life in breast cancer survivors. Health-EpiGEICAM study - Virginia Lope; Ángel Guerrero-Zotano; Nerea Fernández de Larrea-Baz; Silvia Antolín; Marta Benavent Viñuales; Begoña Bermejo; Emma Ruiz-Moreno; José Manuel Baena-Cañada; Lorena París; Antonio Antón; José Ignacio Chacón; Montserrat Muñoz; et al. (Elsevier, 2024)
Objectives: Adherence to healthy lifestyle recommendations has been reported to improve health-related quality of life (HRQL) in breast cancer (BC) patients, but the influence of long-term behavioral changes remains unknown. We evaluated the association between adherence to the 2018 World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) cancer prevention recommendations and HRQL both, at BC diagnosis and the change 7−12 years later. Design: Prospective cohort study. Settings and participants: A total of 406 breast cancer survivors, from the EpiGEICAM study, were recruited in 16 Spanish hospitals. Measurements: Epidemiological, clinical, dietary, physical activity and HRQL information was collected both at recruitment and 7−12 years later. A 7-item score to measure compliance with recommendations was assessed according to the 2018 WCRF/AICR scoring criteria. HRQL was evaluated using SF-36 questionnaire. Linear mixed models for longitudinal data were used to assess the cross-sectional and longitudinal association between adherence score and the physical and mental component summary scores. Results: At diagnosis, for each unit increase in WCRF/AICR score adherence, the HRQL physical domain increased 0.78 points (95%CI: −0.04 to 1.60; P trend:0.06). The mean change in physical HRQL from diagnosis to follow-up per unit increase in within-subject adherence score was 0.73 points (95%CI: −0.18 to 1.65; P trend: 0.12). For the mental domain, no association was observed with compliance with the recommendations at diagnosis, nor with changes in adherence over time. Conclusions: Our results suggest that Increased adherence to WCRF/AICR cancer prevention recommendations over time could contribute to slightly improved long-term physical HRQoL in BC survivors.